Effect of progesterone/estradiol ratio on pregnancy outcome of patients with high trigger-day progesterone levels undergoing gonadotropin-releasing hormone antagonist intracytoplasmic sperm injection cycles: a retrospective cohort study. (17th February 2019) - Golbasi, Hakan; Ince, Onur; Golbasi, Ceren; Ozer, Mehmet; Demir, Mustafa; Yilmaz, Bulent
Abstract: This study investigates the predictive power of serum progesterone/estradiol (P/E2 ) level for estimating the live birth rate in patients who had a serum progesterone (P) rate ≥ 1.5 ng/mL on the human chorionic gonadotropin (hCG) administration day and who received the gonadotropin-releasing hormone (GnRH) antagonist protocol and intracytoplasmic sperm injection (ICSI). This retrospective cohort study included 176 cycles. The P/E2 ratio was lower in patients with a live birth (0.73 ± 0.54) than those without a live birth (1.05 ± 1.38), but the difference was not statistically significant ( p  = .158). According to the receiver operating characteristic curve analysis of the hCG day P/E2 ratio, the area under the curve was 0.579 (95% confidence interval: 0.478 – 0.680, p  = .158) for predicting live birth. In conclusion, this study suggests that a P/E2 ratio is not a significant predictor of a live birth rate in the patients with an hCG-day serum progesterone level of ≥1.5 ng/mL undergoing GnRH antagonist ICSI cycles with a fresh embryo transfer. Impact statement: What is already known on this subject? As the progesterone (P) levels in the late follicular phase correlate with the estradiol (E2 ) levels and the increase in mature follicles, earlier studies have proposed the trigger-day progesterone/estradiol (P/E2 ) ratio as a potential new marker for a premature luteinisation and live birth success. Most of these studies were conducted on long agonist cycles, and found that arbitrarily defined P/E2 ratio of >1 to be associated with poor pregnancy outcomes. What do the results of this study add? This study retrospectively examines the gonadotropin-releasing hormone (GnRH) antagonist cycles with a trigger-day serum P value of ≥1.5 ng/mL undergoing the intracytoplasmic sperm injection (ICSI) treatment. The receiver operating characteristic (ROC) curve analysis did not identify a statistically significant threshold value for the trigger-day P/E2 ratio that was beneficial in predicting a live birth. The P/E2 ratio was also lower in the cycles with a live birth than those without a live birth, although the difference was not statistically significant. What are the implications of these findings for clinical practice and/or further research? The trigger-day P/E2 ratio does not seem to be an efficient prognostic factor for a live birth in the GnRH antagonist ICSI cycles with a trigger-day serum progesterone level of ≥1.5 ng/mL. Further studies are needed to clarify the association of the trigger-day P/E2 ratio and the pregnancy outcomes in GnRH antagonist ICSI cycles.